Positive emotion enhances association-memory - Madan, Christopher R.; Scott, Sarah M.E.; Kensinger, Elizabeth A. (American Psychological Society, 2018)
The influence of emotion on association-memory is often attributed to arousal, but negative stimuli are typically used to test for these effects. While prior studies of negative emotion on association-memory have found impairments, theories suggest that positive emotion may have a distinct effect on memory, and may lead to enhanced association-memory. Here we tested participants’ memory for pairs of positive and neutral words using cued recall, supplemented with a mathematical modeling approach designed to disentangle item- versus association-memory effects that may otherwise confound cued-recall performance. We consistently found enhanced association-memory due to positive emotion. These results provide further evidence that positive information is processed differently than negative and that, when examining association formation, valence as well as arousal must be considered.